2022
DOI: 10.14701/ahbps.21-071
|View full text |Cite
|
Sign up to set email alerts
|

Curative intent radical cholecystectomy followed by hyperthermic intraperitoneal chemotherapy in ruptured intraductal papillary neoplasm of gallbladder with invasive carcinoma

Abstract: Gallbladder cancer has a poor prognosis, especially in peritoneal carcinomatosis related to perforation of the gallbladder followed by bile spillage. Previously, curative-intent treatment was not considered in carcinomatosis from cancer of the biliary tract. A 72-year-old male was referred to the hospital with a perforated gallbladder cancer. Intraoperatively, the tumor was confined to the gallbladder and liver. We presented a case of intention-to-curative resection of perforated gallbladder cancer followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…There is ongoing debate regarding optimal treatment modality of GBC. It is often treated with palliative chemotherapy, but treatment options include curative or palliative chemotherapy, radiotherapy and surgical resection [3,[10][11][12][13]. Surgical management ranges from cholecystectomy alone to complete CRS [3,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is ongoing debate regarding optimal treatment modality of GBC. It is often treated with palliative chemotherapy, but treatment options include curative or palliative chemotherapy, radiotherapy and surgical resection [3,[10][11][12][13]. Surgical management ranges from cholecystectomy alone to complete CRS [3,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…It is often treated with palliative chemotherapy, but treatment options include curative or palliative chemotherapy, radiotherapy and surgical resection [3,[10][11][12][13]. Surgical management ranges from cholecystectomy alone to complete CRS [3,[10][11][12][13]. Some studies have indicated that more aggressive resection achieves longer survival time compared to cholecystectomy alone, and we have presented a case where the survival time after CRS with HIPEC is almost 3 years longer than the median survival time for GBC [12,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations